The Evolution of a Nation: How Geography and Law Shaped the American States - Daniel Berkowitz, Karen B. Clay (Princeton University Press, 2011)
Countries around the world exhibit striking differences in per capita income. For example, in 2008, income in the United States, Singapore, and Switzerland was roughly forty times higher than income in Nepal and Uganda. There are also differences within countries. In the United States in 2000 income in the state of Connecticut was almost twice as high as income in the state of Mississippi. In Russia, income in the city of Moscow was six and a half times higher than income in the neighboring Ivanovo oblast.1 What drives the disparities? The disparities appear to be driven in part by political and legal institutions.2 Political institutions such as legislatures influence key aspects of the economy, including the rights individuals hold vis-Ã -vis land, labor, capital, materials, and intellectual property. Legal institutionsâ€”in particular courtsâ€”play an integral role in defining and enforcing rights. This discussion pushes the question back one level. What drives differences in political and legal institutions across countries? A recent literature suggests that differences in institutions and income are driven by a combination of geographic and historical factors. Gallup, Sachs, and Melllinger (1998), Mellinger, Gallup, and Sachs (2000), Sachs and Malaney (2002), Sachs (2003), and Nunn and Puga (2009) argue that geography influences income through its effects on public health, productivity, trade costs, population growth, and investment. Diamond (1997) makes the case that distance from historically critical trade routes and centers of knowledge influences income through its impact on the diffusion of technology and knowledge. Several studies argue that geography and the disease environment at time of settlement have influenced the character of institutions in former European colonies. Engerman and Sokoloff (1997 and 2005) argue that climate and soil shaped the subsequent character of political institutions. In colonies that were warm and rainy and had soil suitable for sugar and other staples, â€œbadâ€ political institutions representing the narrow interests of wealthy elites emerged. In colonies that were colder and dryer and had different soil conditions, â€œgoodâ€ political institutions representing broader interests were established. Acemoglu, Johnson, and Robinson (2001) provide evidence that the disease environment at time of settlement shaped the quality of institutions that protect property rights. In colonies where early settlers had a good chance of surviving, â€œgoodâ€ institutions that protected property rights and limited the power of the government to expropriate emerged. By contrast, in colonies where early settlers were likely to contract life-threatening diseases, â€œbadâ€ institutions that allowed settlers to easily extract resources emerged.